THE PORTRAYAL OF AFRO-AMERICAN STRUGGLE AGAINST RACISM IN SELMA FILM - Merlin Octafiani Ruata; Chris Asanti; Fatimah Muhajir (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
Racism is a belief that some groups are superior and some groups are inferior. One of the literary works that tells about racist is Selma film. Selma is a film directed by Ava Du Vernay, written by Paul Webb, and was released in 2014. The film is talking about racism issues that happened in America in 1965. The entitled of this research is the portrayal of Afro American struggle against racism in Selma film formulate two research questions about kinds of racism and the way Afro- American people struggle against racism in Selma film. The purposes of this research is find out about kinds of racism and the way Afro-American people struggle against racism in Selma film. In this research, the researcher used descriptive qualitative method and racism theory. Furthermore, the data were generated from the script, dialogues, and the scenes in the film. The results of this research found two kinds of racism: individual racism and institutional racism. The finding also showed ways of struggle against racism, they are: coercion and refusal, domination and escape, subjectification and creation. The struggle of Afro- American was represented by characterization of the characters which showed racism treatment in the Film.